Reliability of Clinical Aspect and Transaminases Level as a Guidance for Screening for Sero-positive Hepatitis C in Multi-transfused β-Thalassaemia Patients - Abbas, Abdulrazzaq Mustafa; Mahmood, Najdat Shukur; Al-Azzawi, Dawood Salman (Diyala Journal of Medicine, 2019)
Background: Although regular blood transfusion enhances the overall survival of thalassaemia patients, it have a significant threat of infection with transfusion-related infections, including hepatitis C; therefore, screening is mandatory. Routine screening with anti-hepatitis C Ab was recommended many years ago; sometimes they depend on level of liver enzymes. Objective: To evaluate the clinical and biochemical features of seropositive hepatitis C virus infection in multi-transfused β-thalassaemia patients to verify if they can be used as a guidance for screening. Patients and Methods: A retrospective- study done from June to September of 2014 at Thalassaemia Center in Baqubah city - Diyala province - Iraq. All registered β- thalassaemia major and intermedia patients were included, involving adults. Enzyme linked immunosorbant assay was used to screen for hepatitis C virus. Symptoms, signs, and biochemical features, including liver transaminases level, of sero-positive patients were gathered and analyzed. Descriptive statistical analysis and Pearson chi- square test was appliedto analyze data by using Statistical Package for Social Sciences software, version 16. Results: The total enrolled subjects were 215, male gender comprises 54.9% (n=118); most of the included patients were under 12 years old. The results indicate that 11.2%(n= 24) of multi-transfused β- thalassaemia patients showed serological evidence of hepatitis C. The highest anti-HCV prevalence was observed at ≥ 18 years old patients (p value=.000). More than two third of cases were male gender (p value=.041), but the gender was not associated with positive serology for hepatitis C in the whole sample of the study (p value=.096). All anti-HCV positive patients were clinically asymptomatic; biochemically, 75% (n=18) of them had normal liver transaminases levels (p value=. 014). Conclusion: Asymptomatic clinical status and unreliable transaminases level elevation cannot be helpful as directory for screening, we encourage the continuation of the usual routine screening test by enzyme linked immunosorbant assay for hepatitis C in β-thalassemia patients; it is more crucial for an older patient.